OPTIMIZATION OF PARALLEL LINKS IN REDUNDANT UTILITY STRUCTURES: Array - Usenko, V.; Kodak, O.; Nikolaenko, V.; Usenko, I. (Municipal economy of cities. Series: «Economy science», 2022)
The publication states that an important problem in the design, operation and reconstruction of various networks of engineering infrastructure is to determine the reliability of structurally complex systems. Modeling the reliability of technical systems seems to be a rather complex task. It is emphasized that the ways of rational redundancy of a complex structure of systems presuppose the well-known method of minimal paths and connections. The problem of the optimal arrangement of a system with a redundant structure has certain limitations in accordance with the available resources, such as the lower value of the probability of the system’s connectivity, which serves as an optimization criterion. The paper investigates a system with identical components. The article discusses many possible forms of the structure of the system. Structural reliability expressions are calculated for all combinations used in determining the lower and upper values ​​of structural reliability. In the process of constructing a redundant structure, it is necessary to determine a variant of its form, which maximizes the value of reliability under the established restrictions on the available resources invested in the construction and operation of the system using the cost parameter for some form of its structure. The peculiarity of the system reliability function is considered when it increases, which has a discrete argument and consists of a number of some functions. In the presented geometric model, a number of operations are used to determine and concretize the requirements for the variants of the forms of the components of the system under study for their different properties, and the forms that do not meet these conditions for the variants of the component in terms of resources are removed. Here the requirements for the probability of connectivity are defined, according to which unsuccessful forms of possible structures of the system are removed. The work uses an algorithm to extract from a set of reasonable options for some options for components by resources. The specified variant of the structure form is assumed to be optimal according to the criteria. If the number of variants of the structure shape is large enough, then to find the optimal solution, another algorithm is used, in which the value of the objective function is checked, which determines the conditions for the probability of connectivity in design decisions. It is noted that in practical application the obtained solutions can be approximate.